ADULT NUTRITIONAL STATUS ASSESSMENT: CROSS SECTIONAL FOLLOW UP STUDY IN A UNITED KINGDOM HOSPITAL. (8th June 2013) - Shah, D; Dhanjal, S; Lunt, S; Cussens, C; Kadri, S
Abstract : Introduction: Malnutrition in hospital is widely under-recognised (1). In 2011 a cross sectional study was carried out into nutritional status assessments at a UK District General Hospital. Out of 100 patients only 55% had a MUST (Malnutritional Universal Screening Tool) assessment on admission. Aims/Background: Following the implementation of trust-wide training, monthly spot checks and detailed guidelines on nutrition management, a follow up study was conducted to assess the impact of these changes on nutritional care. Method: Ten patients were randomly selected from the same ten wards used in the initial study, encompassing Medicine, Care of the Elderly and Surgery. For each patient, completion of MUST assessments, nutrition care plans, food and fluid charts were recorded. One ward was excluded from the study due to an outbreak of norovirus which led to ward closure. The data was analysed using Microsoft Excel. Results: 73% (66/90) of patients had MUST assessments on admission compared with 55% previously. Of these, 32% were deemed medium (9/66) or high risk (12/66) for malnutrition. Of these 'at risk' patients, 57% (12/21) and 62% (13/21) had fully completed food and fluid charts respectively, compared with 59% and 59% previously. Only 57% had nutrition care plans daily. Conclusion: Whilst there was an improvement in the number of completed MUST assessment on admission, there was no change in the number of fully completed food and fluid charts for those patients at risk of malnutrition. The aim of these on-going assessments is to identify 'at-risk' patients on admission, optimise nutrition early, and try to reduce complication rates, length of stay, and mortality rates across the Trust (2). The results of this six month follow-up are positive but further cycles of training and reiteration of the importance of nutritional assessment are required. There will be ongoing audits arranged by the nutrition team and nursing staff to assess clinical indicators for fluid and nutrition, based on guidance from Essence of Care, NICE Guidelines, and Trust Guidelines.